Does Telomere Shortening Precede the Onset of Hypertension in Spontaneously Hypertensive Mice?. (12th August 2016) - Chiu, Christine L.; Hearn, Nerissa L.; Paine, Devin; Steiner, Nicole; Lind, Joanne M.
Abstract : Telomere length is widely considered as a marker of biological aging. Clinical studies have reported associations between reduced telomere length and hypertension. The aim of this study was to compare telomere length in hypertensive and normotensive mice at pre-disease and established disease time points to determine whether telomere length differs between the strains before and after the onset of disease. Genomic DNA was extracted from kidney and heart tissues of 4-, 12-, and 20-week-old male hypertensive (BPH/2J) and normotensive (BPN/3J) mice. Relative telomere length (T/S) was measured using quantitative PCR. Age was inversely correlated with telomere length in both strains. In 4-week-old pre-hypertensive animals, no difference in T/S was observed between BPH/2J and BPN/3J animals in kidney or heart tissue (kidney p = 0.14, heart p = 0.06). Once the animals had established disease, at 12 and 20 weeks, BPH/2J mice had significantly shorter telomeres when compared to their age-matched controls in both kidney (12 weeks p < 0.001 and 20 weeks p = 0.004) and heart tissues (12 weeks p < 0.001 and 20 weeks p < 0.001). This is the first study to show that differences in telomere lengths between BPH/2J and BPN/3J mice occur after the development of hypertension and do not cause hypertension in the BPH/2J mice.